Effect of vitamin C on the survival, moulting and whole body ascorbic acid content of Macrobrachium rosenbergii (de Man) juveniles - Ittoop, Gijo; Jose, Susheela (Indian Journal of Fisheries, 2011)
An experiment was conducted to find out the influence of dietary vitamin C on the survival, moulting rate and tissue ascorbic acid content of Macrobrachium rosenbergii juveniles. Vitamin C was fed in a semi purified diet at eight levels @ 0, 45, 67.5, 90, 112.5, 135, 180 and 450 mg AAE (ascorbic acid equivalent)/kg to the experimental animals for 56 days. The results showed that below a level of 67.5 mg AAE/kg diet, the survival rate was very poor mainly due to incomplete moulting. Black lesions were observed at the tip of the appendages of dead animals. Above 90 mg AAE/kg diet, survival and moulting rates were satisfactory. The whole body ascorbic acid content reached a steady state only at 135 mg AAE/kg diet and hence the minimum amount of ascorbic acid recommended in the diet of M. rosenbergii is 135 mg AAE/ kg.